Madonna, “sex” e o fetichismo pós-moderno - Gusmão, Roney (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
This text is one of the postdoctoral research products developed at the Instituto de Sociologia of the Universidade do Porto, aiming to understand how pop culture icons translate postmodern values. Here we are interested in observing how “Sex” reifies contemporary hedonism, and for this we resort to the concept of fetish in Freud and Marx to analyze discourses of power in their dialectical relationship with the ethos of the system. “Sex” translates the needs of fugitive sensory experiences into a society hungry for the eccentric and superficial, being interpreted as an expression of a time.